(untitled) (Journal of Philosophy Culture and Political Science, 2018)
This article is dedicated to the monograph of Zh.Zh. Moldabekov “Intellectual nation: strategic policy and factors of cultural and national formation.” Authors analyze the actual problems of formation of intellectual nation considered in the monograph. Authors show the importance of social and cultural factors for the development of innovation, the formation of human capital, modernization of society. Authors reveal the role and influence of cultural processes and valueson the social and economic modernization, systematic reformation of society in the new global reality. According to the authors the monograph of Professor Zh.Zh. Moldabekovis devoted to actual issues of formation of intellectual nation, it presents the theoretical and methodological problems of modernization of Kazakhstan society. The book is of interest to researchers, humanities scholars, to everyone who is concerned about prospects of development of our society and cultural dynamics. Key words: society, culture, civilization, science, education, values, innovation, modernization, intellectual nation, human capital.